DNA Lesion Alters Global Conformational Dynamics of Y-family DNA Polymerase during Catalysis - Maxwell, Brian A. (American Society for Biochemistry and Molecular Biology, 2012)
A major product of oxidative damage to DNA, 8-oxo-7,8-dihydro-2′-deoxyguanine (8-oxoG), can lead to genomic mutations if it is bypassed unfaithfully by DNA polymerases in vivo. However, our pre-steady-state kinetic studies show that DNA polymerase IV (Dpo4), a prototype Y-family enzyme from Sulfolobus solfataricus, can bypass 8-oxoG both efficiently and faithfully. For the first time, our stopped-flow FRET studies revealed that a DNA polymerase altered its synchronized global conformational dynamics in response to a DNA lesion. Relative to nucleotide incorporation into undamaged DNA, three of the four domains of Dpo4 undertook different conformational transitions during 8-oxoG bypass and the subsequent extension step. Moreover, the rapid translocation of Dpo4 along DNA induced by nucleotide binding was significantly hindered by the interactions between the embedded 8-oxoG and Dpo4 during the extension step. These results unprecedentedly demonstrate that a Y-family DNA polymerase employs different global conformational dynamics when replicating undamaged and damaged DNA.